Predictors of Parental Coping During the Covid-19 Pandemic: A Survey in Germany - Clemens, Vera; Köhler-Dauner, Franziska; Ziegenhain, Ute; Fegert, Jörg M. (Frontiers in Psychology, 2021)
The Covid-19 pandemic has been profoundly affecting nearly everybody, but families with minors have been hit particularly. Closure of schools and kindergartens, home schooling, and working from home has led to a profound upheaval in family life. Parental adverse childhood experiences (ACEs) are an important determinant for parenting behaviour. Importantly, ACEs can increase the vulnerability to stress and impair coping strategies. Therefore, we aimed to assess the role of ACEs and sociodemographic predictors on parental coping during the current pandemic. In a cross-sectional online survey, 687 parents of minors in Germany were included. Demographic and psychosocial predictors for parental coping during the first lockdown due to the Covid-19 pandemic were assessed. Results show that younger age of the respective child, income loss, dissatisfaction with the sharing of childcare duties and ACEs were significantly associated with an increase of potential harmful parenting behavior during the Covid-19 pandemic. An increase of dissatisfaction with the sharing of childcare duties during the pandemic was predicted by working from home and taking care of the children mainly by oneself, while sharing childcare duties with the partner equally resulted even in an increase of satisfaction with sharing of childcare duties during the pandemic. These findings demonstrate that an own history of childhood adversity is a risk factor for harmful parenting during the pandemic. Parental satisfaction with sharing of caregiving is an important factor for parental coping during the pandemic. Sharing of caregiving between partners should be encouraged.